2014
DOI: 10.1002/jnr.23452
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow doses of cannabinoid drugs protect the mouse brain from inflammation‐induced cognitive damage

Abstract: In our previous studies, we found that a single ultralow dose of tetrahydrocannabinol (THC; 0.002 mg/kg, three to four orders of magnitude lower than the conventional doses) protects the brain from different insults that cause cognitive deficits. Because various insults may trigger a neuroinflammatory response that leads to secondary damage to the brain, the current study tested whether this extremely low dose of THC could protect the brain from inflammation-induced cognitive deficits. Mice received a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 71 publications
2
42
0
Order By: Relevance
“…Conversely, THC agonizes CB1Rs in high-density areas (Pertwee, 2008), and leads to alterations in neuroinflammatory processes when administered during adolescence, resulting in a pro-inflammatory shift in the hippocampus during adulthood following repeated adolescent injection (Zamberletti et al, 2015; Moretti et al, 2015). Moderate increases in inflammatory and stress responses are also seen following an acute saline administration, whereas stress response, neuroinflammation, and prolonged single-housing have been shown to reduce performance in the NOR task (Võikar et al, 2005; Carey et al, 2009; Fishbein-Kaminietsky et al, 2014; Freiman et al, 2016). The ability of THC to protect against disruption of novel object discrimination in adult treated mice may have been due to reduced neuroinflammatory responses across treatment that were present in the adult control- and adolescent THC-treated mice, in part due to stress response and CB1R receptor levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, THC agonizes CB1Rs in high-density areas (Pertwee, 2008), and leads to alterations in neuroinflammatory processes when administered during adolescence, resulting in a pro-inflammatory shift in the hippocampus during adulthood following repeated adolescent injection (Zamberletti et al, 2015; Moretti et al, 2015). Moderate increases in inflammatory and stress responses are also seen following an acute saline administration, whereas stress response, neuroinflammation, and prolonged single-housing have been shown to reduce performance in the NOR task (Võikar et al, 2005; Carey et al, 2009; Fishbein-Kaminietsky et al, 2014; Freiman et al, 2016). The ability of THC to protect against disruption of novel object discrimination in adult treated mice may have been due to reduced neuroinflammatory responses across treatment that were present in the adult control- and adolescent THC-treated mice, in part due to stress response and CB1R receptor levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Given the current trends in cannabinoid research, combining THC with cannabidiol may work to reduce these deficits. Cannabidiol is recognized for its lack of psychoactive effects, stimulation of hippocampal cell proliferation and neurogenesis, and has been demonstrated to reduce novel object memory impairment in other models that produce neuroinflammation (Pertwee, 2008; Fagherazzi et al, 2012; Fishbein-Kaminietsky et al, 2014; Campos et al, 2015; Schiavon et al, 2016). With the use of medical cannabis on the rise, it is important to understand how the addition of cannabidiol to THC may mediate negative side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of healthy populations have not found adverse cognitive effects following abstinence (Grant, Gonzalez, Carey, Natarajan, & Wolfson, 2003; Jager, Kahn, Van Den Brink, Van Ree, & Ramsey, 2006), whereas others have reported acute as well as long-term effects on cognition when compared to non-users (Abdullaev, Posner, Nunnally, & Dishion, 2010; Battisti et al, 2010; Gonzalez et al, 2012; Grant, Chamberlain, Schreiber, & Odlaug, 2012; Lisdahl & Price, 2012; Solowij et al, 2002; Thames, Arbid, & Sayegh, 2014; Tapert, Granholm, Leedy, & Brown, 2002). Furthermore, animal studies of Alzheimer’s disease and neuroinflammation-induced cognitive damage support the neuroprotective effects of cannabinoids (Fishbein-Kaminietsky, Gafni, & Sarne, 2014; Ramírez, Blázquez, Gómez del Pulgar, Guzmán, & de Ceballos, 2005). …”
Section: Introductionmentioning
confidence: 89%
“…Several studies showed that CBD has anti-inflammatory properties [242246] and can produce beneficial effect in acute inflammation and chronic neuropathic states [5, 247, 248]. THC demonstrates anti-inflammatory effect via activation of the CB1 receptor [249251]. In addition, cannabinoids provide anti-inflammation effect by reducing the vasoconstriction and restoring blood supply to the injured area [252].…”
Section: Beneficial Effects Of Cannabinoids In the Amelioration Ofmentioning
confidence: 99%